The Influence of Digital Comic Learning Media on Primary School Students’ Motivation in Social Studies - Safira Mirosunnaily; Puri Pramudiani (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2021)
This study aims to determine the influence of digital comics learning media on primary school students’ motivation in social studies. The method used in this research was experimental quantitative research. The subjects of this research were fourth grade students at MIT Fatahillah Depok, namely class IV A as control class and class IV B as experimental class, totaling 29 students for each class. The instruments used in this research were in the form of questionnaires and documentation. The data was validated using correlation product moment and to test the reliability used Cronbach Alpha. After the data was declared valid and reliable, it was continued with the calculation of the normality test using the Liliefors test and the homogeneity test using the Fisher test. The results of hypothesis testing in this study used the t test and obtained tcount was 4.392 and ttable was 1.673. Therefore, this study proves that there is an influence of using digital comics learning media on primary school students’ motivation in social studies.Keywords: Learning Media, Digital Comic, Motivation, Social Studies, Primary School.